2012
DOI: 10.1007/s11033-012-1477-3
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA protects PC12 cells from β-amyloid25–35-induced apoptosis via PI3K/Akt signaling pathway

Abstract: For the aging populations of any nation, Dementia is becoming a primary problem and Alzheimer’s dementia (AD) is the most common type. However, until now, there is no effective treatment for AD. Tanshinone IIA (Tan IIA) has been reported for neuroprotective potential to against amyloid β peptides (Aβ)-induced cytotoxicity in the rat pheochromocytoma cell line PC-12, which is widely used as AD research model, but the mechanism still remains unclear. To investigate the effect of Tan IIA and the possible molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Accumulating evidence has proved that PI3K/AKT/mTOR and MAPK signaling pathways are closely related to cell proliferation and apoptosis [ 33 , 34 ]. PC12 cell apoptosis, induced by sodium nitroprusside or β-amyloid, has been reported to be repressed through PI3K/AKT/mTOR pathway [ 35 , 36 ]. Likewise, cell apoptosis of PC12 cells could be suppressed by nobiletin [ 37 ] or gastrodin [ 38 ] through MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has proved that PI3K/AKT/mTOR and MAPK signaling pathways are closely related to cell proliferation and apoptosis [ 33 , 34 ]. PC12 cell apoptosis, induced by sodium nitroprusside or β-amyloid, has been reported to be repressed through PI3K/AKT/mTOR pathway [ 35 , 36 ]. Likewise, cell apoptosis of PC12 cells could be suppressed by nobiletin [ 37 ] or gastrodin [ 38 ] through MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigation is needed to unravel the signaling mechanisms of tanshinone IIA against glutamate neurotoxicity as other pathways may also be involved in the neuroprotective effect of tanshinone IIA. For example, tanshinone IIA is shown to protect PC12 cells against amyloid β -protein-induced apoptosis via the PI3K/Akt signaling pathway, an important survival mechanism which is also implicated in glutamate excitotoxicity [12, 61]. …”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA (Tan IIA) is one of the main active ingredients extracted from the rhizome of the Salvia miltiorrhiza . Recent studies have elucidated the neuroprotective action and molecular mechanism of Tan IIA in vitro and in vivo, including AD . Recently, some reports have indicated that Tan IIA dramatically activated the ERK signalling pathway and induced autophagic cell death .…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA has been extensively used in the treatment of cardiovascular disease and cerebrovascular disease . Additionally, Tanshinone IIA has been suggested efficacious in preventing memory deficits by ameliorating neuronal damage and protecting against Aβ 25–35 ‐induced neurotoxicity and the pathological features of AD . Of interest, a recent study demonstrated that Tanshinone IIA could markedly induce autophagic cell death in KBM‐5 leukaemia cells .…”
Section: Introductionmentioning
confidence: 99%